Biovalorization of Friedelane Triterpenes Derived from Cork Processing Industry Byproducts (Journal of Agricultural and Food Chemistry, 2006)
Here, we describe the synthesis, bioactivity screening, and structure?activity relationships of various synthetic triterpenoids prepared from the cork processing byproducts friedelin (1) and 3-hydroxyfriedel-3-en-2-one (2) via oxidative procedures. The synthesis of compounds 2α-trimethylsiloxyfriedelan-3-one (17), friedelin-2,3-lactone (18), friedelin-3-oxime (19), and friedelin-3,4-lactam (20) is also described. We have studied the insecticidal and phytotoxic potential of these compounds, their selective cytotoxic effects on insect and mammalian cells, and their antiparasitic effects. Structural modifications of the A-ring of friedelin (1) improved its insecticidal activity with derivatives 5, 2,3-secofriedelan-2-al-3-oic acid (6), its acetylated derivative 6a, 3?- and 3α-hydroxyfriedelane (9 and 10), 3α-hydroxyfriedel-2-one (11), 4?-hydroxyfriedel-3-one (16), the acetylated 10a, 3,4-secofriedelan-4-oxo-3-oic-acid (14), lactone 18, and the oxime 19 being stronger insecticides than the parent compound. Methyl-3-nor-2,4-secofriedelan-4-oxo-2-oic acid (12) and its acetylated derivative 12a also showed insecticidal activity in contrast to their inactive parent compound 2. The postingestive effects and cytotoxicity of these compounds suggest a multifaceted insecticidal mode of action. These structural modifications did not result in better phytotoxic agents than the parent compounds except for lactam 20 and yielded several moderately active antiparasite derivatives (seco acids 6, 12, 14, and 4? -hydroxyfriedel-3-one 16) with cytotoxic effects on mammalian cells. Keywords: Quercus suber; cork smoker wash solids; triterpene friedelanes; Spodoptera littoralis; Lactuca sativa; Trypanosoma cruzi; Leishmania infantum; antifeedant; phytotoxic; antiparasitic
doi: 10.1021/jf0531151